Permainan Tradisional Dalam Membentuk Karakter Anak Usia Dini - Tuti Andriani (Lembaga penelitian dan pengabdian kepada Masyarakat, 2012)
Superior human resources is the most valuable asset for any country. Indonesia has the largest population-3 in the world, has the human resource potential is very large. When empowered with the best it can enhance the welfare of the people of Indonesia. One of the Government's efforts in empowering human resources to manage the education sector is becoming more professional. The most basic education sector in the personal formation of human resources (HR) in Indonesia, is through a program of Early Childhood Education (early childhood). One period to the early penciri is the Golden Age, which at this time all the potential of the fastest growing child. One way to increase the potential of children at an early age is to play. Because the slogan in early childhood education is